Alzheimer's disease pathology: pathways between chronic vascular risk factors and blood-brain barrier dysfunction in a cohort of patients with different types of dementia - Gan, Jinghuan; Yang, Xia; Zhang, Guili; Li, Xudong; Liu, Shuai; Zhang, Wei; Ji, Yong (Frontiers in Aging Neuroscience, 2023)
Background Blood brain barrier (BBB) breakdown is considered a potential mechanism of dementia. The Alzheimer's disease (AD) biomarkers and vascular factors are also associated with BBB permeability. Objective In the present study, the combination effects of neuropathological biomarkers of AD and chronic vascular risk factors for BBB were investigated. Methods The cerebrospinal fluid (CSF)/serum albumin ratio (Qalb), an indicator of BBB permeability, was measured in a total of 95 hospitalized dementia patients. The demographics, clinical information, and laboratory tests were collected from the inpatient records. The CSF neuropathological biomarkers of AD and apolipoprotein E (APOE) genotype were also collected. The mediation analysis model was used to calculate the associations among neuropathological biomarkers of AD (mediator), the Qalb, and chronic vascular risk factors. Results Three types of dementia, AD (n = 52), Lewy body dementia (LBD, n = 19), and frontotemporal lobar degeneration (n = 24), were included with a mean Qalb of 7.18 (± 4.36). The Qalb was significantly higher in dementia patients with type 2 diabetes mellitus (T2DM, p = 0.004) but did not differ based on the presence of APOE ε4 allele, CMBs, or amyloid/tau/neurodegeneration (ATN) framework. The Qalb was negatively associated with the levels of Aβ1-42 (B = −20.775, p = 0.009) and Aβ1-40 (B = −305.417, p = 0.005) and positively associated with the presence of T2DM (B = 3.382, p < 0.001) and the levels of glycosylated hemoglobin (GHb, B = 1.163, p < 0.001) and fasting blood glucose (FBG, B = 1.443, p < 0.001). GHb is a direct chronic vascular risk factor for higher Qalb (total effect B = 1.135, 95% CI: 0.611–1.659, p < 0.001). Ratios of Aβ1-42/Aβ1-40 or t-tau/Aβ1-42 were mediators of the association between the Qalb and GHb; the direct effect of GHb on the Qalb was 1.178 (95% CI: 0.662–1.694, p < 0.001). Conclusion Glucose exposure can directly or indirectly affect BBB integrity through Aβ and tau, indicating glucose affects BBB breakdown and glucose stability plays an important role in dementia protection and management.